Costs of Perico (Coryphaena Hippurus) freezing for the improvement of the quality of life of artisanal fishermen in Peru - Milón Guzmán, Juan José (2021)
2021 6th International Conference on Sustainable and Renewable Energy Engineering, ICSREE 2021